Intensified Niagara leaf filtration via in-situ ultrasonic wave fields - Mohd Yunus, Rosli; Junin, Radzuan; Sulaiman, Ahmad Ziad; Abdul Aziz, Ramlan; Ngah, Mokhtar; Nasir, Abu Samah; Sethpa, Mohd Sabri (Faculty of Chemical and Natural Resources Engineering, UTM, 2001)
Niagara Leaf Filter unit is commonly used for the separation of bleaching agent from the `Refined Bleached Deodorized' (RBD) oil in the edible/vegetable oil industry. In general, the time required to separate 500 kg bleaching agent from the treated oil is approximately 2 Â½ hours after which the system is totally filled with solid particles and the system needs to be regenerated. A typical regeneration process of the system takes approximately 1Â½ hours. The sequence of filtration and regeneration process is repeated for approximately two to three weeks, depending on the condition of the filter medium, before a thorough cleaning method is conducted which last for a period of five to seven days. In view of the long downtime of the filtering operation system, this study is conducted to investigate the possibility of intensifying the filtration operation with the assistance of ultrasound wave fields. In this paper, the effect of ultrasound on the rate of filtration of activated clay in oil suspension is presented. The degree of filtration rate enhancement as a function of solids concentration in the feed is also discussed. In general, the ultrasound field improves the filtration rate by minimizing the thickness of the filter cake, and hence reducing the resistance of fluid flowing through the filter medium. The solids concentration has a negative impact on the degree of filtration improvement as a result of ultrasound wave fields.